Consequences of Ecotourism in Nepal - Acharya, Suresh (Rural Development Journal, 2017)
Ecotourism focuses on ecological resource, environmental conservation, community development and economic development by maintaining low-impact and non-consumptive use of local resources. Various forms of ecotourism have emerged globally, including community-based ecotourism, ecosystem ecotourism, cultural ecotourism, nature-based ecotourism, protected area ecotourism, and rural ecotourism. Ecotourism, which prioritizes the conservation of natural resources, biodiversity, and the sustainability of ecosystems, yields more positive impacts on the environment, society, and culture than negative ones. It fosters social cohesion and mobility, strengthens traditional cultures and hospitality, and mitigates political conflicts. Economically, it generates direct employment in hospitality sectors like hotels, lodges, and tourist restaurants, playing a crucial role in the development strategies of many nations, particularly those in the process of development. For instance, in Nepal, ecotourism contributes significantly to enhancing forest cover, biodiversity, and other environmental benefits such as alternative energy sources. Moreover, it plays a pivotal role in poverty alleviation, rural development, agricultural transformation, community enrichment, and empowering women. However, during the initial stages of ecotourism development, challenges may arise in engaging adequate private agencies and local communities in providing accommodations, food services, tour management, and other tourism activities, especially during peak visitation periods. This study focused to the study of ecotourism in Nepal and its impacts on different sectors of the Nepalese society.